The Population Size of the Lesser bandicoot (Bandicota bengalensis) in Three Markets in Penang, Malaysia - Nurul Liyana Khairuddin,; Razlina Raghazli,; Shahrul Anuar Md Sah,; Nur Juliani Shafie,; Nur Munira Azman, (Tropical Life Sciences Research, 2011)
A study of the population size of Bandicota bengalensis rats in three markets in Penang was conducted from April 2004 through May 2005. Taman Tun Sardon Market (TTS), Batu Lanchang Market (BTLG) and Bayan Lepas Market (BYNLP) were surveyed. Six sampling sessions were conducted in each market for four consecutive nights per session. The total captures of B. bengalensis in TTS, BTLG and BYNLP were 92%, 73% and 89% respectively. The total population of B. bengalensis in TTS was estimated as 265.4 (with a 95% confidence interval of 180.9–424.2). The total population at BTLG was estimated as 69.9 (with a 95% confidence interval of 35.5–148.9). At BYNLP, the total population was estimated as 134.7 (with a 95% confidence interval of 77.8–278.4). In general, adult male rats were captured most frequently at each site (55.19%), followed by adult females (31.69%), juvenile males (9.84%) and juvenile females (3.27%). The results showed that the number of rats captured at each site differed significantly according to sex ratio and maturity (?2 = 121.45, df = 3, p<0.01). Our results suggest that the population sizes found by the study may not represent the actual population size in each market owing to the low numbers of rats recaptured. This finding might have resulted from the variety of foods available in the markets. Satu kajian mengenai saiz populasi tikus Bandicota bengalensis telah dijalankan di tiga buah pasar di Pulau Pinang iaitu Pasar Taman Tun Sardon (TTS), Pasar Batu Lanchang (BTLG) dan Pasar Bayan Lepas (BYNLP). Sebanyak enam sesi persampelan telah dijalankan di setiap pasar selama empat hari berturut-turut bagi setiap sesi. Di ketiga-tiga kawasan kajian, sebanyak 92%, 73% dan 89% daripada keseluruhan tikus yang ditangkap terdiri daripada jenis B. bengalensis. Jumlah anggaran populasi tikus B. bengalensis di TTS sebanyak 265.4 (dengan 95% selang keyakinan di antara 180.9– 424.2), 69.9 (dengan 95% selang keyakinan di antara 35.5–148.9) di BTLG dan 134.7 (dengan 95% selang keyakinan di antara 77.8–278.4) di BYNLP. Secara amnya, tikus jantan paling banyak ditangkap di setiap kawasan kajian (55.19%), diikuti tikus betina (31.69%), tikus juvenil jantan (9.48%) dan tikus juvenil betina (3.27%). Hasil kajian menunjukkan terdapat perbezaan signifikan dalam bilangan tangkapan tikus berdasarkan nisbah jantina dan kematangan (?2 = 121.45, df = 3, p<0.01) di setiap kawasan kajian. Hasil dari keputusan kami berpendapat bahawa saiz populasi daripada kajian ini berkemungkinan tidak menggambarkan saiz populasi yang sebenar untuk setiap pasar, kerana hasil tangkapan semula tikus yang rendah. Ini berkemungkinan disebabkan oleh kelimpahan makan yang pelbagai yang terdapat di pasar tersebut.